Stages of change in physical exercise behavior among adolescents Estágios de mudança de comportamento relacionados ao exercício físico em adolescentes - da Viana M.S.* (2010)
The objective of the present study was to analyze the stages of behavioral change (SBC) in physical exercise among adolescent from public schools in Florianopolis, SC, Brazil. The sample consisted of 400 adolescents (53.8% girls and 46.2% boys) aged 14 to 18 (mean age of 16.3 years for girls and 16.4 years for boys), who were randomly selected from state high schools operating in the municipality of Florianopolis. Associations between variables were analyzed using the chi-square test (α=0.05). The results showed that 67.6% of the students performed regularly some type of physical exercise (action and maintenance stages), whereas only 9.8% did not exercise or did not intend to exercise (pre-contemplation stage). Boys exercised more than girls since they were in more advanced SBC (p<0.000). Age, school year, or period of study was not significantly associated with EMC in the sample as a whole, but male students who studied in the morning were found to be more sedentary (p=0.050). The results showed that most students of the population perform some physical exercise. However, attention should be paid to a minority of students who showed a sedentary behavior, especially those who do not intend to exercise. The importance of SBC for more effective health intervention is highlighted since, even if a program does not render an individual physically active within a short period of time, positive long-term behavioral changes can be expected.